STRATEGI GURU DALAM PEMBELAJARAN BERPIKIR KRITIS PESERTA DIDIK MELALUI UNIT KEGIATAN BELAJAR MANDIRI MATA PELAJARAN PPKn (Studi di SMA Negeri 3 Surakarta) - Novita Taya Sara; Rusnaini Rusnaini; Winarno Winarno (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2019)
The research aims to find out: 1) The strategy of teachers in student’s critical thinking learning using self learning activity in Pancasila and Citizenship Education in SMA Negeri 3 Surakarta; 2) Teacher’s supporting factors and inhibitory factor in critical thinking learning using self learning activity in Pancasila and Citizenship Education in SMA Negeri 3 Surakarta.They study uses a qualitative approach, a type of qualitative descriptive research. Data sources are obtained from the informant, place and document. Sampling techniques using purposive sampling. Data collection techniques using interviews, observations, and document analysis. Data validity using trianggulation data and Trianggulation method. Analyze data using interactive analysis models.Result of the research: 1) The strategy of teachers in student’s critical thinking learning using self learning activities in Pancasila education subjects and citizenship in Pancasila and Citizenship Education in SMA Negeri 3 Surakarta: a) Teacher need to learn and understand about the components development and characteristics of self learning activities ; b) The teacher makes a learning activity by displaying questions of Higher Order Thinking Skills (HOTS); c) The teacher makes the look of self learning activity; and d) The teacher designed the planning, implementation, and evaluation activities. 2) The teacher's supporting factor in student’s critical thinking learning using self learning in Pancasila Education and Citizenship course includes: a) schools facilities; b) The positive response from the students with the self learning activity; c) Learning activities in the self learning activities lead to the growing Higher Order Thinking Skills (HOTS) that support critical thinking skills; d) Self learning activities as a self-learning strategy that helps learners achieve learning submission. The inhibitory factor includes internal factors: a) The feeling of fear of self-learners; b) lack of ability to communicate students; and c) lack of motivation in the students in the interest of the study of Pancasila and the citizenship. External factors include: a) The responses of nearby friends who often laugh at other learners when they wrong answer; b) Limited time allocation; c) Learners who have completed self learning activity of Pancasila and Citizenship Education must wait for other learners to get new material taught by the teacher and; d) Find it difficult to print the modul for the self learning activity of Pancasila and Citizenship Education because of the limited fund of the school.Keywords: Strategies, Critical Thinking, Self Learning Activity, Pancasila Education and Citizenship